Manufacturing of novel aerogel based thermal coating systems for carbon/epoxy composite substrates. - Krishnaswamy, Suryanarayanan (Cranfield University, 2018)
To try and increase the applicability of carbon fibre composites, the present work considers the use of thermal coatings on its surface. After a study on relevant literature pertaining to conventional and alternate thermal barrier coatings, it was believed that YSZ-based and/or aerogel-based systems had the most potential. But successful application of these coatings required additional research, particularly on processing routes and long-term performance. Therefore to try and achieve a more efficient thermal coating on composite substrates, aerogel-based materials were investigated since they showed the most promise. These aerogel/polymer composites were further characterized using different morphological, optical and thermal techniques. The experimental results showed particularly promising trends for aerogel/epoxy materials whose best sample had an aerogel damage coefficient value of 18.3%. Hence, this system was applied as a coating on a carbon fibre reinforced polymer substrate and the whole system showed better thermal performance compared to a pure epoxy coating. The coating and the substrate were subsequently modelled and solved using finite element analysis to determine the most effective system under a cyclic thermal load. Although, the selection of the coating type (double, top or bottom) is dependent on the exact application; the top coating displayed the best performance balance. Nevertheless, both, experimental measurements and simulation results in the current work point to a potential application of the coating in industries such as aerospace, automotive and/or construction.
Keywords: Composites; aerogels; coating; thermal conductivity; finite element analysis; damage coefficient